Environmentally affected people. Towards a conceptualization in the context of struggles for recognition - Berger, Mauricio (2016)
This paper proposes a situated reflection on the political potential of the concept of those environmentally affected, in a framework of fight for rights, in order to promote a dense conceptualization, according to the situations of suffering and violations suffered by victims of environmental pollution. First we describe an experience rich in examples, highlighting the institutional set of the injustices andthose devices of mis-recognition. Also we describe the communities formed by and for the victims. Secondly, we make a review of some contexts of use of the notion of environmental affected that can contribute to strength —in the particular case analyzed and by extension, to others— for a public and political self-understanding towards effective recognition.